Morphological tuning of Eu2O2S nanoparticles, manifestation of peroxidase-like activity and glucose assay use. (17th December 2015) - Ghosh, Abhisek Brata; Saha, Namrata; Sarkar, Arpita; Dutta, Amit Kumar; Biswas, Papu; Nag, Kamalaksha; Adhikary, Bibhutosh
Abstract : We present a single source precursor driven synthesis of Eu2 O2 S with variable shapes, which effectively mimic peroxidase activity, and were successfully employed to selectively detect and determine glucose. Abstract : Eu2 O2 S nanoparticles have been synthesized by solvothermal decomposition of the precursor complex [NHEt3 ] + [Eu(acda)4 ] −, wherein acda − is the anion of 2-aminocyclopentene-1-dithiocarboxylic acid. Oleylamine alone or in combination with surface active agents, such as trioctylphosphine or oleic acid, at 280 °C produced nanoparticles of three different morphologies, namely, ultrathin nanoplates, nanospheres and short rods. The optical band energy of the nanoparticles has been found to be 4.57(8) eV. Eu2 O2 S particles exhibit strong photoluminescence at room temperature with a quantum yield of about 4% upon excitation at 285 nm. All three forms display peroxidase-like activity towards the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine in the presence of H2 O2 and follow a Michaelis–Menten enzymatic pathway. The mechanistic investigation reveals that the Eu 3+ /Eu 2+ redox couple plays a crucial role behind this catalytic process. Catalytic efficiency of the nanoparticles decreases in the order plates > spheres > rod-like particles. Based on peroxidase activity, selective detection and estimation of glucose in the presence of related carbohydrates has been carried out.